Lung cancer incidence trends in Uruguay 1990–2014: An age-period-cohort analysis. (August 2018) - Alonso, Rafael; Piñeros, Marion; Laversanne, Mathieu; Musetti, Carina; Garau, Mariela; Barrios, Enrique; Bray, Freddie
Highlights: Uruguay has one of the highest lung cancer rates worldwide. The country initiated comprehensive anti-smoking measures in 2005. Lung cancer incidence rates in men declined in the past 25 years. Predictions indicate that incidence will rise for some years among women. Results probably do not reflect recent tobacco control initiatives. Abstract: Background: Uruguay, a country with one of the highest lung cancer rates worldwide, initiated a series of comprehensive anti-smoking measures in 2005. We assess the tobacco control policies in the context of cohort-driven lung cancer incidence trends over a 25-year period, providing baseline predictions to 2035. Methods: Using data from the National Cancer Registry of Uruguay, an age-period-cohort analysis of trends 1990–2014 was performed. The NORDPRED package was used to predict the annual number of new cases of lung cancer and incidence rates up to 2035. Results: In men, age-standardised (world) rates declined from a peak of 165.6 in 1995 to 103.1 by 2014, translating to a 70% reduction in the risk of lung cancer in men born in 1970 relative to the early-1940s. In females, rates increased steadily from 18.3 in 1991 to 30.0 by 2014, with successive increases in risk among generations of women born 1940–1960. There is however evidence of a decline in observed rates in women born recently. Extrapolations of the trends indicate an 8% reduction in the mean number of new lung cancer cases in men by 2035, but a 69% increase in women. Conclusion: Despite observed and predicted reductions in lung cancer incidence in Uruguayan men, rates among women are set to continue to increase, with a large rise in the annual number of female lung cancer diagnoses expected before 2035. There are signals of a diminishing risk among recent generations of women born after 1960. The current analysis provides important baseline information in assessing the future impact of the recent tobacco control initiatives in Uruguay.